Pengaruh Kombinasi Aromaterapi Peppermint Dan Mobilisasi Dini Pasif Terhadap Nausea Vomitingpost General Anestesi Di RSUD Soedono Madiun Provinsi Jawa Timur - Tyas Prasdina Wardaningrum, Cindy; Marsaid; Hidayah, Nurul; Supono, Supono (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: To determine the effect of a combination of peppermint aromatherapy and early passive mobilization on nausea vomiting post general anesthesia. Methods: The research design was Quasi Experimental pre test and post test control group. The total research sample was 36 respondents. The intervention provided was a combination of peppermint aromatherapy and passive early mobilization. Nausea and vomiting were measured using the RINVR instrument. Analysis used the bivariate paired t test. Results: The results of the study on nausea and vomiting after general anesthesia before the intervention were 13 (72%) respondents experiencing severe nausea and vomiting and after the intervention it decreased to 7 (%) respondents with moderate nausea and vomiting. In this study, a paired t-test was used with a p value of 0.008, which showed a decrease in the level of nausea and vomiting in post general anesthesia patients after being given the intervention. Conclusion: The conclusion is that there is an effect of a combination of peppermint aromatherapy and passive early mobilization on Nausea Vomiting Post General Anesthesia at RSUD dr. Soedono Madiun. It is hoped that health workers will provide interventions using a combination of peppermint aromatherapy and passive early mobilization to reduce nausea and vomiting in post general anesthesia patients.